Whiteness, scapegoating, and scarcity: medicalizing ‘the US Opioid Crisis’ - Pettus, Katherine (2020)
This paper characterizes the successful civil lawsuits brought by sub-national units of government in the US against multinational pharmaceutical companies to recover the costs of public expenditures (goods and services) incurred as they attempt to manage the ‘opioid crisis,’ as a scapegoating strategy whose function is to deflect attention from the governance failures that allow corporate colonization of the public sphere and rescue the moribund privileges of whiteness enjoyed by the ‘blue collar aristocracy’ until neoliberal globalization rendered them obsolete. Recent drops in white life expectancy, which are associated with chronic diseases and non-medical opioid use, map onto high unemployment and under-employment rates in formerly prosperous communities, now fodder for populist political campaigns. Criminalizing the pharmaceutical companies and executives for peddling prescription medicines to inadequately trained (in the treatment of pain) physicians — some of whom prescribed opioids inappropriately to (majority white) patients/consumers, some of whom developed addictions, and/or poisoning following non-medical use or consumption with alcohol or illicit substances —medicalizes the white opioid crisis and identifies consumers as victims. This distinguishes them from the Americans of color whose ‘drug use’ has been criminalized, who have been disproportionately arrested, and sentenced to long periods of incarceration that entail the loss of civil and political rights, including the right to vote. White elites staked out the ‘color line’ before the Founding, perpetuating it through various scapegoating and ‘shapeshifting’ strategies to the present day. The lawsuits are only the most recent iteration of a morally bankrupt carceral state